Pentingnya Insecurity untuk Mengatasi serta Menyadarkan Kesadaran Diri Agar Tampil Lebih Percaya Diri - Djenap Zamilummi Polhaupessy; Edy Soesanto; Muhammad Dzaky Fadli (International Forum of Researchers and Lecturers, 2025)
Insecure in Indonesian means unsafe. Meanwhile, according to the APA Dictionary of Psychology, insecurity or insecurity is a feeling of inadequacy and lack of self-confidence. While self-awareness is the ability to understand and recognize one's own emotions, strengths, weaknesses, values, and motivations, the implementation of self-awareness in social and emotional learning (SEL) is very important to help students develop emotionally and socially. Meanwhile, self-confidence is confidence and belief in one's abilities, being optimistic, objective, responsible, rational and realistic to solve and overcome a problem with an upside down situation so that it can provide something and be accepted by other people and the environment. Insecurity is sometimes necessary in everyday life to increase self-awareness and grow self-confidence. Many cases often occur among teenagers throughout the world, factors also come from the surrounding environment, whether it be friends or sometimes even family.